The Risks of Children Violence A Case Study Based on Social and Demographic Factors in Kalimas River Area Surabaya - Rahayu, Aristiana Prihatining; Hamsia, Waode (International Research-Based Education Journal, 2018)
The purpose of this study is to describe how children experience violence. Some factors are highlighted to affect this issue including family dysfunction, economic, and misperceptions on how these children to be educated. This research used a qualitative approach involving some descriptive analysis. Results found that residents specifically children who live in slum and populated area potentially have more violent experiences. These probably relate to physical, psychological or emotional, and verbal. Children with poorly educated and uneducated parents, unemployed, less knowledge on religious practices potentially experience the violence. Further, children whose young parents and from a big family would have a bad experiences in the past since they had a very limited attention from their parent.Keywords: child violence, social factors, demography